Gender typicality of occupational aspirations among immigrant and native youth: the role of gender ideology, educational aspirations, and work values - Gambaro, Ludovica; Wilhelm, Janna; Schober, Pia Sophia (Frontiers in Sociology, 2023)
This study investigates variations in the gender typicality of occupational aspirations among adolescents of immigrant and non-immigrant backgrounds at around age 16 in four European countries. Despite the theoretical importance attributed to gender beliefs and work-related values in sociological and psychological conceptual framework, few empirical studies have examined the role of gender ideologies and values about work in relation to the gender typicality of occupational choices. Drawing on a representative sample of 8,574 students from different backgrounds in England, Germany, the Netherlands, and Sweden, we explore how their gender ideologies, educational aspirations, and the importance they attributed to a job affording high income, the possibility to help others, or the possibility to think and solve problems relate to the gender typicality of their aspired occupations. Our findings show that boys and girls of immigrant origins aspired to somewhat less gender typical occupations than their majority peers. Among girls, these differences would be even larger if they were not suppressed by the more traditional gender ideologies held by girls of immigrant backgrounds. In terms of mediating mechanisms, our findings suggest that the more ambitious educational aspirations may partly explain these differences. More broadly these findings indicate that distinguishing multiple dimensions of adolescents’ work-related values may hint to different underlying mechanisms in the formation of adolescents’ occupational aspirations.